English Romantic poets and the Enlightenment - Orel, H (Voltaire Foundation, 2017)
I. The Cotter's Saturday night and rival literary traditions II. Blake's hostility to the Enlightenment III. Coleridge and the conversation poems IV. Wordsworth's repudiation of Godwinism V. Scott's definition of the usable past VI. Byron's debt to the Enlightenment VII. Keats's faith in human progress VIII. Shelly I. The Necessity of atheism IX. Shelly II. The Last great poem of the English Enlightenment